Establishing the Aus-ROC Australian and New Zealand out-of-hospital cardiac arrest Epistry. Issue 4 (5th April 2016) - Beck, Ben; Bray, Janet; Smith, Karen; Walker, Tony; Grantham, Hugh; Hein, Cindy; Thorrowgood, Melanie; Smith, Anthony; Smith, Tony; Dicker, Bridget; Swain, Andy; Bailey, Mark; et al.
Abstract : Introduction: Out-of-hospital cardiac arrest (OHCA) is a global health problem with low survival. Regional variation in survival has heightened interest in combining cardiac arrest registries to understand and improve OHCA outcomes. While individual OHCA registries exist in Australian and New Zealand ambulance services, until recently these registries have not been combined. The aim of this protocol paper is to describe the rationale and methods of the Australian Resuscitation Outcomes Consortium (Aus-ROC) OHCA epidemiological registry (Epistry). Methods and analysis: The Aus-ROC Epistry is designed as a population-based cohort study. Data collection started in 2014. Six ambulance services in Australia (Ambulance Victoria, SA Ambulance Service, St John Ambulance Western Australia and Queensland Ambulance Service) and New Zealand (St John New Zealand and Wellington Free Ambulance) currently contribute data. All OHCA attended by ambulance, regardless of aetiology or patient age, are included in the Epistry. The catchment population is approximately 19.3 million persons, representing 63% of the Australian population and 100% of the New Zealand population. Data are collected using Utstein-style definitions. Information incorporated into the Epistry includes demographics, arrest features, ambulance response times, treatment and patient outcomes. The primary outcome is 'survival to hospital discharge', with 'return of spontaneous circulation' as a key secondary outcome. Ethics and dissemination: Ethics approval was independently sought by each of the contributing registries. Overarching ethics for the Epistry was provided by Monash University HREC (Approval No. CF12/3938—2012001888). A population-based OHCA registry capturing the majority of Australia and New Zealand will allow risk-adjusted outcomes to be determined, to enable benchmarking across ambulance providers, facilitate the identification of system-wide strategies associated with survival from OHCA, and allow monitoring of temporal trends in process and outcomes to improve patient care. Findings will be shared with participating ambulance services and the academic community.